If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 22 = -3x + 31 Reorder the terms: 22 + 6x = -3x + 31 Reorder the terms: 22 + 6x = 31 + -3x Solving 22 + 6x = 31 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 22 + 6x + 3x = 31 + -3x + 3x Combine like terms: 6x + 3x = 9x 22 + 9x = 31 + -3x + 3x Combine like terms: -3x + 3x = 0 22 + 9x = 31 + 0 22 + 9x = 31 Add '-22' to each side of the equation. 22 + -22 + 9x = 31 + -22 Combine like terms: 22 + -22 = 0 0 + 9x = 31 + -22 9x = 31 + -22 Combine like terms: 31 + -22 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 2x+10=x+25 | | 7y+(-3)=-17 | | x^2+5x-24=0 | | x^2+5-24=0 | | 8x-7=-4x+5 | | -4=2x-12 | | 9=27x | | x^2-16x+63=0 | | 44=x+21 | | 15x+.33y=-71.67 | | -8(n+3)-12(n-2)=-7n-8n | | 17=12-x | | x^2-13x+30=0 | | -8(n+3)-12(n-2)=-7-8n | | x^2+5x-14=0 | | -10(k+8)=-10k+136 | | x^2+5-14=0 | | 4x-2y=5 | | 2(a+9)=7a+6(8a+3) | | x^2+7=18 | | 9x^2-81=0 | | 11(8x-4)=2(11x+11) | | 2x+1+2x+1-2x=4 | | x^2-14x+49=0 | | 3(5-2n)=29-4n | | x^2-2x-8=0 | | x^2+6x+7=0 | | -(3-b)=2b | | 2(x+4)-7x=28-x | | 2(x+4)-7x=28 | | 6x^2+7x-5=0 | | 4x+17=25 |